Synergy between the Multiple Supply Chain and Green Supply Chain Management (GSCM) approaches: an initial analysis aimed at fostering supply chain sustainability - de Carvalho, Ana Lima; Ignácio, Livia Rodrigues; Esposto, Kleber Francisco; Ometto, Aldo Roberto (European Journal of Sustainable Development, 2016)
The concept of Green Supply Chain Management (GSCM) was created in the 90s to reduce the environmental impacts of productive systems. This approach seeks to improve the environmental performance of all the participants in a supply chain, from the extraction of raw materials to the use and final disposal of the product, through relationships of collaboration or conformity between the parties. The multiple supply chains approach established by Gattorna (2009) brought to light different supply chain configurations based on the segmentation of customers into four psychological types: collaborative, innovative, efficient and dynamic. Given the recency of these approaches, there are still many opportunities to explore their interrelationships and devise ways for incorporating GSCM practices into different supply chains. Based on an analysis of the literature, this paper presents an initial overview of the synergy between GSCM practices and the four multiple supply chain configurations proposed by Gattorna. In the preliminary discussion of this paper, it was concluded that the Continuous Replenishment and Lean supply chains are more likely to incorporate the GSCM approach in their operations, while the Agile and Fully Flexible supply chains are less receptive to GSCM concepts. Keywords: Supply Chain Management, SCM, Multiple Supply Chains, Green Supply Chain Management, GSCM.